COST OF ILLNESS PASIEN DIABETES MELLITUS TIPE 2 JKN NON PBI DI INSTALASI RAWAT INAP RUMAH SAKIT ISLAM SULTAN AGUNG SEMARANG PERIODE JANUARI-DESEMBER 2022 - Finda Hamidah; Yustisia Dian Advistasari; Wulan Kartika Sari (Parapemikir : Jurnal Ilmiah Farmasi, 2023)
Diabetes mellitus is a group of metabolic diseases characterized by hyperglycemia resulting from defects in insulin secretion. Diabetes Mellitus is classified into several types, namely type 1 diabetes mellitus, type 2 diabetes mellitus, gestational diabetes mellitus, and other types of diabetes mellitus. Treatment of diabetes mellitus requires a large amount of money because it requires a lifetime of treatment and frequent co-morbidities. The purpose of this study was to determine the characteristics of patients with type 2 diabetes mellitus and to determine the average direct medical costs in patients with type 2 diabetes mellitus with or without comorbidities at the inpatient installation of RSI Sultan Agung Semarang in 2022. The results of this study were 84 patients who met the inclusion criteria with a total of 43 female patients and 41 male patients. The most dominant age range is in the age range of 55-65 years. The type 2 diabetes mellitus patients with comorbidities with a total of 80 patients with 34 types of comorbidities of IDR 4,202 .124. Type 2 diabetes mellitus patients with the most comorbidities were type 2 diabetes mellitus patients with hypertension comorbidities with a total of 17 patients.